ANALYSIS OF GREEN BANKING, LEVEL OF FINANCIAL LITERACY, AND ENVIRONMENTAL AWARENESS TOWARDS CUSTOMER LOYALTY OF SYARIAH BANKS WITH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE - Najwa Syafira; Muhammad Iqbal Fasa (Institut Binamadani Indonesia, 2026)
The shifting business paradigm demands that the Islamic banking industry focus not only on profitability but also on actively contributing to ecosystem sustainability through the adoption of green banking practices. Furthermore, internal customer factors, such as financial literacy and ecological sensitivity, are crucial determinants in responding to the sustainability values ​​offered by banking institutions. This study aims to analyze the conceptual framework linking green banking implementation, financial literacy, and environmental awareness to Islamic bank customer loyalty, with customer satisfaction as a mediating variable. Using a structured Systematic Literature Review (SLR) approach, a comprehensive search of scientific articles was conducted in the Scopus and Google Scholar databases covering publications from 2021–2026. After rigorous screening based on inclusion and exclusion criteria, 45 final articles were selected and synthesized using qualitative descriptive methods. The results of the synthesis indicate that green banking, financial literacy, and environmental awareness have a partial positive and significant effect on customer loyalty. Furthermore, customer satisfaction has been consistently shown to act as a mediator, bridging the three independent variables in strengthening long-term loyalty. Aligning personal ecological values ​​with a bank's green commitment is a key catalyst in creating a satisfying banking experience. As a practical implication, Islamic bank management is recommended to authentically integrate green principles into daily operations, expand Sharia-compliant financial education, and transparently communicate environmental initiatives to optimize customer engagement.